An application of Monitoring and Numerical Modelling in Open Stope Mining - Friday R. G; Palmer W. T; Thomson I. R R (The Australasian Institute of Mining and Metallurgy, 1981)
The paper introduces the problems encountered in designing open stopes and briefly examines the factors that determine the final stope dimensions achieved after mining is completed. A case study is presented where monitoring of a stope was considered necessary due to the expected formation of a highly stressed crown pillar above the stope. The influence, on the mining approach adopted, of a yielding crown pillar is discussed. Monitoring and numerical modelling were used to develop an understanding of the behaviour of the particular stope as mining progressed. A comparison between the measured displacements and the numerical predictions at an interim stage of mining was carried out to assist in choosing the final sequences involved in completing the stope.